Actuarial review of the National Insurance Fund as of 31 December - 2001- : the Bahamas (The National Insurance Board Nassau, 2002)
Reviews past experience. Provides projections of the NIB's income, expenditure and reserves under three scenarios and makes recommendations.
Documentation Centre has 2001; 2011